When you're back - Glines, Abbi. (New York : ATRIA Paperback, 2015)
A chance meeting in Rosemary Beach has turned into a fairy-tale romance as Reese prepares to move in with Mase on his family ranch in Texas. With the loving support of the Colts, and her recent discovery that she has family of her own, Reese can finally move on from the dark horrors of her past and into a bright future. But Aida isn't going to let that happen. The beautiful blonde has been raised to think of Mase as her cousin, but it's clear to Reese that Aida doesn't love Mase like a cousin should. And then there's Captain, who has connections in Dallas and Rosemary Beach--and who conveniently shows up wherever Reese happens to be. Hot, mysterious, and plain-speaking, Captain isn't afraid to tell Reese what he thinks about Mase--and how he feels about her. As the competition for Mase and Reese's hearts heats up, Reese's past begins to unravel, illuminating shocking truths that will forever change the lives of the happy couple--and set the final stories of Rosemary Beach in motion.
Keywords: ROMANCE FICTION -- MAN-WOMAN RELATIONSHIPS